COLLABORATION BETWEEN UNIVERSITIES AND GOVERNMENTS IN REALIZING QUALITY POLICIES, (EVIDENCE-BASED POLICY) - Darniyus, Al Adly; Warsono, Hardi (Journal of Governance and Public Policy, 2020)
In the policy formulation process, there is a gap between universities and the government as policy makers, which causes the existence of policies that are not evidence based. Many background this gap, including the lack of validity of information from the results of tertiary research so that it is unable to increase the government's confidence to accommodate the information. On the one hand there is still strong political influence in policy formulation. lobbying system, compromise to bargaining to determine whether or not the policy is decided. Therefore, this paper aims to see the collaboration of universities and government in producing quality policies. The author uses the method of library study, which is collecting data, information, by examining research journals, books, literature and sources of reliable sources both written and digital that are relevant and relevant to this paper. The results of the study indicate that universities have not been able to meet the needs of quality policies. This much of the information from research results has not been able to open up the confidence of policy makers. as a result of the study are only small input and are more dominated by political interests. Therefore, one of the efforts that must be addressed is involving the government in the research design process, this will increase the confidence of policy makers regarding the information obtained.